PENGEMBANGAN BAHAN AJAR PJBL-STEAM BERBASIS KEWIRAUSAHAAN UNTUK MENINGKATKAN CRITICAL THINKING MATEMATIS SISWA SMK - Dian pramodyowati; In in supianti; Rani Siti Fitriani; Mardiah Hafizah Muhammad Hafizi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
Vocational high school students' low mathematical critical thinking and the limited availability of project-based mathematics teaching materials that integrate STEAM with entrepreneurship contexts remain major challenges in mathematics education. This study aimed to develop entrepreneurship-integrated Project-Based Learning (PjBL)–STEAM mathematics teaching materials to enhance students' mathematical critical thinking. It employed a Research and Development (R&D) approach using the ADDIE model, which comprises five phases: analysis, design, development, implementation, and evaluation. The participants were 24 tenth-grade students at a vocational high school in Majalengka Regency, West Java, Indonesia. Data were collected using expert validation sheets, a mathematical critical thinking test, interview protocols, and a student response questionnaire. The quality of the materials was assessed in terms of validity, practicality, and effectiveness. The results showed that the materials were valid and practical, both in the strong category, and effective in improving students' mathematical critical thinking, with the improvement reaching the high category. This study contributes to the development of STEAM-based mathematics teaching materials by integrating entrepreneurship-oriented projects into mathematics learning, thereby providing an instructional alternative for fostering mathematical critical thinking among vocational high school students.